تداول الأدوات المالية الإسلامية في سوق الخرطوم للأوراق المالية - علام, عثمان; مولاي, بوعلام; حملة, عزالدين (جامعة الوادي - University of Eloued, 2019)
ملخص: تقدم هذه الورقة البحثية الصناعة المالية الإسلامية في السودان، بإعطاء نظرة حول النظام المالي في السودان ومراحل تدرجه للتوجه إلى النظام المالي الإسلامي في جميع عملياته، وكذا الإشارة للسوق الخرطوم للأوراق المالية وأهم الصكوك المتداولة فيه، وأهمية هذا التداول في تزايد القيمة السوقية للبورصة. لقد عملت الحكومة السودانية على تعزيز المالية الإسلامية بسوق الخرطوم للأوراق المالية بإصدار عديد الصكوك المالية الإسلامية، لتشهد القيمة السوقية قفزة ب 18,63 مليار جنيه بين عام 2001-2017، ما يبرز أن السودان قد رسم صورة مشرفة لصناعة المال الإسلامي جعلت منه مثال لتجربة رائدة في الصناعة المالية الإسلامية. تصنيف JEL: G23 ، E44 ، F65، G15 Abstract: This paper presents the Islamic financial industry in Sudan with an overview of the financial system in Sudan and its stages of orientation to the Islamic financial system in all its operations, as well as the reference to Khartoum Securities Market and the most important instruments traded in it, and the importance of this trading in increasing the market value of the stock exchange. The Sudanese government has worked to strengthen Islamic finance in the Khartoum Stock Exchange by issuing a number of Islamic sukuks. The market value witnessed a leap of 18.63 billion pounds between 2001 and 2017, highlighting that Sudan has painted an honorable image of the Islamic finance industry, which made him an example of a all experience in the Islamic finance industry. Classification JEL ; G23 ، E44 ، F65، G15.
Trading of Islamic financial instruments in the Khartoum Stock Exchange
مقال
Keywords: النظام المالي السوداني، ; المالية الإسلامية، ; الصكوك الإسلامية ; سوق الخرطوم للأوراق المالية